Combinatorial screening for therapeutics in ATTRv amyloidosis identifies naphthoquinone analogues as TTR-selective amyloid disruptors - Sasaki, Ryoko; Suico, Mary Ann; Chosa, Keisuke; Teranishi, Yuriko; Sato, Takashi; Kagami, Asuka; Kotani, Shunsuke; Kato, Hikaru; Hitora, Yuki; Tsukamoto, Sachiko; Yamashita, Tomohiro; Yokoyama, Takeshi; et al. (Journal of pharmacological sciences, 2023)
Hereditary ATTR amyloidosis is caused by the point mutation in serum protein transthyretin (TTR) that destabilizes its tetrameric structure to dissociate into monomer. The monomers form amyloid fibrils, which are deposited in peripheral nerves and organs, resulting in dysfunction. Therefore, a drug that dissolves amyloid after it has formed, termed amyloid disruptor, is needed as a new therapeutic drug. Here, we first established a high throughput screening system to find TTR interactors from the LOPAC1280 compound library. Among the hit compounds, thioflavin T-based post-treatment assay determined lead compounds for TTR amyloid disruptors, NSC95397 and Gossypol, designated as B and R, respectively. Because these compounds have naphthoquinone-naphthalene structures, we tested 100 naphthoquinone derivatives, and found 10 candidate compounds that disrupted TTR amyloid. Furthermore, to determine whether these 10 compounds are selective for TTR amyloid, we evaluated them against beta-amyloid (Aβ1-42). We found two compounds that were selective for TTR and did not disrupt Aβ-derived amyloid. Therefore, we succeeded in identifying TTR-selective amyloid disruptors, and demonstrated that naphthoquinone compounds are useful structures as amyloid disruptors. These findings contribute to the on-going efforts to discover new therapeutic tools for TTR amyloidosis.